Hollow Core Bar Micropiles - Design Parameters Interpreted From 260 Load Tests - Jesús E. Gómez (Deep Foundations Institute, 2007)
A recent bridge underpinning project provided a unique opportunity to obtain information on the load-deflection response of 260 hollow-core bar micropiles. All production micropiles were proof-tested to a maximum load of 125 percent of the design load. In addition, four verification tests were performed on sacrificial micropiles to at least two and a half times the design loads. This paper presents the results of the verification and proof tests performed for this project, and provides recommended values for design of hollow core bar micropiles in soils similar to those encountered. This work shows that hollow core bar micropiles provide a significant unit bond capacity in both granular and fine soils, which may be greater than that typically expected in pressure-grouted (Type B) micropiles. The hollow core bar system allows faster installation rates in the soil types encountered than other traditional micropile techniques, and can be installed with relatively simple quality control procedures.